Business Plan - PercuPad - Tan, Tze Wei (2016)
Introduction With all the technological advancements in today’s society, musical products - especially with traditional instruments such as the guitars, pianos and violins - have always been the same for many centuries. Although electronic alternative versions of these instruments exist, some may not wish to compromise the classical tone. Therefore, PercuPad is a Start-up company which plans to produce the most innovative musical products the world has yet to see. The following plan explains the market, our value proposition and our market segmentation strategy. The detailed financial plans provide a clear view of the sales and profit forecasts. These plans show how PercuPad will reach profitability in the 2nd year of operation and generate shareholder return on equity within five years. Product PercuPad’s first product, called the “PercuBox”, is an innovative musical product add-on to most current instruments to enhance the playing experience. Its use is not limited to just instruments, as it can be also used in many different applications according to the users’ creativity. It is a physical product that integrates 10 attachable/detachable wireless touch sensors, which the user can stick on to most surfaces (or instruments) and can produce a wide variety of sounds and effects when touched. The product is in early development stage and plans to be completed within the first 18 months of operation. The product will be assembled locally in the UK by an engineering manufacturing company and the stock suppliers will be purchased from both the UK and primarily from China. The product mainly targets the UK but it is available for oversees deliver through PercuPad’s selected carriers (FeDex, transglobal and DHL). PercuPad’s pricing strategy considers the cost of its competitor, development cost and cost of sales. Which brings up to be £300 (including VAT and shipping), this price is approximately the same in comparison with the current competitor pricing. Although PercuPad has only 1 line of product, it has the ability and potential to create many more innovative products using this technology. Market The estimated revenue of musical instruments in the UK is at £422million and is expected to grow up to £469.2million with an annual growth rate 2.6%. This market can be divided into a few segments, and the leading growth within the category is amplification and DJ equipment of 15.5% of the total market share. Current market trend is shifting towards a more technological era such that the use of social media and better technological expectation of gadgets are on the rise. Moreover, the additional funding from the government in music education brought an increase of 28% in exposure to music and instrumental learning since 1999; not to mention the average disposable income in the UK that is rising steadily due to the increase in employment. With this, PercuPad’s main targets are students, hobbyist, and professional musicians primarily the age between 18-47 years who use social media and have an average annual disposable income of £30,000 and above. The current main direct competitors are ACPAD followed by numerous indirect competitions from portable speaker (Bose, Beats, Betron and Anker), Loop pedals (Boss, DigiTech, Electro Harmonix and Hotone) and synthesizer companies (Moog and Korg). Objectives The main primary objectives of PercuPad are to: • Obtain a funding of £250,000 for the use over the next 2 years to cover start-up cost and initial operating expenses • Develop a consumer ready product by the end of 18 months by hiring necessary skills at specific parts of the process to save cost. • Raise a minimum of £100,000 from the public using crowdfunding platforms (Kickstarter, Indiegogo and tilt) and also spread awareness by the end of the 18th month of operation. • Generate a net profit of £190,000 by the end of the 2nd financial year. Financial highlights In order to bring PercuPad to life, it requires an initial start-up funding of £250,000 in exchange for 20% equity. Sales of the product will only begin after development is complete (approximately 18 months) and can expect to generate profit from the 2nd financial year. Sales are expected to grow until the 3rd year and drop slowly after.